CO2-Induced Transcriptional Reorganization: Molecular Basis of Capnophillic Lactic Fermentation in Thermotoga neapolitana - d’Ippolito, Giuliana; Landi, Simone; Esercizio, Nunzia; Lanzilli, Mariamichella; Vastano, Marco; Dipasquale, Laura; Pradhan, Nirakar; Fontana, Angelo (Frontiers in Microbiology, 2020)
Capnophilic lactic fermentation (CLF) is a novel anaplerotic pathway able to convert sugars to lactic acid and hydrogen using CO2 as carbon enhancer in the hyperthermophilic bacterium Thermotoga neapolitana. In order to give further insights into CLF metabolic networks, we investigated the transcriptional modification induced by CO2 using a RNA-seq approach. Transcriptomic analysis revealed 1601 differentially expressed genes (DEGs) in an enriched CO2 atmosphere over a total of 1938 genes of the T. neapolitana genome. Transcription of PFOR and LDH genes belonging to the CLF pathway was up-regulated by CO2 together with 6-phosphogluconolactonase (6PGL) and 6-phosphogluconate dehydratase (EDD) of the Entner-Doudoroff (ED) pathway. The transcriptomic study also revealed up-regulation of genes coding for the flavin-based enzymes NADH-dependent reduced ferredoxin:NADP oxidoreductase (Nfn) ) and NAD-Ferredoxin oxidoreductase (Rnf) that control supply of reduced ferredoxin and NADH and allow energy conservation-based sodium translocation through the cell membrane. These results support the hypothesis that CO2 induces rearrangement of the central carbon metabolism together with activation of mechanisms that increase availability of the reducing equivalents that are necessary to sustain CLF. In this view, this study reports a first rationale of the molecular basis of CLF in T. neapolitana and provides a list of target genes for the biotechnological implementation of this process.